Explorations in Cilicia, The Neilson Expedition: Fifth Interim Report Excavations at Mersin: 1938-39, Part 111 - Garstang, J.
= The Iron Age; Part IV = The Late and Middle Bronze Ages; with Contributions by S. Lloyd, R. Barnett, G. M. Fitz Geraid.